Rational application of the ESPGHAN 2022 recommendations for the follow-up of the paediatric coeliac patient: consensus document of scientific societies (SEGHNP, AEPAP, SEPEAP, SEEC, AEG, SEPD, SEMFYC, SEMG and SEMERGEN) - Enriqueta Roman; Josefa Barrio; Maria Luz Cilleruelo; Ricardo Torres; Vega Almazán; Cristobal Coronel; Beatriz Espin; Eva Martinez-Ojinaga; David Perez Solís; Maria Antonia Moreno; Joaquín Reyes; Luis Fernandez Salazar; et al. (Anales de Pediatría (English Edition), 2024)
Coeliac disease is a common condition for which the only current treatment is a gluten-free diet. Adherence to this diet is not always easy and is associated with a reduction in quality of life for the patient and their family. Non-adherence is associated with complications of varying severity. The lack of control at the outpatient care level in a high percentage of these patients evinces the need to improve follow-up protocols and the approach to care delivery with coordination of paediatric gastroenterology units (PGU) and primary care paediatricians. With this aim in mind, the present document was developed by consensus to offer a set of recommendations adapted to our region, based on the recent recommendations published by the European Society of Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN), and with participation of the pertinent scientific societies, including those concerning the adult population, for the management and follow-up of adolescents and the transition to adult care. Resumen: La enfermedad celíaca es una patología frecuente y cuyo único tratamiento en el momento actual es la dieta sin gluten. El seguimiento de esta dieta no siempre es fácil e implica limitaciones en la calidad de vida del paciente y su familia. La no adherencia se asociaría a complicaciones de distinta gravedad. La falta de control de estos pacientes en consultas en un alto porcentaje de casos plantea la necesidad de mejorar los protocolos de seguimiento y de abordarlos de forma coordinada entre las Unidades de Gastroenterología Pediátrica (UGP) y los pediatras de Atención Primaria. Con ese objetivo se han consensuado en este documento, basándose en las recomendaciones recientemente publicadas por la Sociedad Europea de Gastroenterología, Hepatología y Nutrición Pediátrica (ESPGHAN), un conjunto de recomendaciones adaptadas a nuestro entorno y contando con la participación de las Sociedades Científicas implicadas, incluyendo a las Sociedades de adultos para el abordaje del seguimiento del adolescente y de la transición de cuidados a los profesionales de adultos.